2007
DOI: 10.1529/biophysj.106.102400
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of TBA Block of the TRPV1 Channel

Abstract: The transient receptor potential vanilloid 1 (TRPV1) channel is a nonselective cation channel activated by capsaicin and responsible for thermosensation. To date, little is known about the gating characteristics of these channels. Here we used tetrabutylammonium (TBA) to determine whether this molecule behaves as an ion conduction blocker in TRPV1 channels and to gain insight into the nature of the activation gate of this protein. TBA belongs to a family of classic potassium channel blockers that have been wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 72 publications
5
49
0
Order By: Relevance
“…In Xenopus laevis oocytes, we have found that lidocaine and QX-314 exert biphasic effects on TRPV1 channels, inhibiting capsaicin-evoked TRPV1 currents at lower (micromolar) concentrations and activating TRPV1 channels at higher (millimolar) concentrations. Whereas the mechanisms are unknown, studies into the permeation and gating pathway of TRPV1 have found, similar to results obtained with Kv channels, that permanently charged quaternary ammonium compounds are able to potently block TRPV1 intracellularly, thus delimiting similarities among these seemingly disparate family members (Oseguera et al, 2007;Jara-Oseguera et al, 2008). However, it remains unclear whether TRPV1 is also susceptible to extracellular inhibition by quaternary ammonium compounds.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In Xenopus laevis oocytes, we have found that lidocaine and QX-314 exert biphasic effects on TRPV1 channels, inhibiting capsaicin-evoked TRPV1 currents at lower (micromolar) concentrations and activating TRPV1 channels at higher (millimolar) concentrations. Whereas the mechanisms are unknown, studies into the permeation and gating pathway of TRPV1 have found, similar to results obtained with Kv channels, that permanently charged quaternary ammonium compounds are able to potently block TRPV1 intracellularly, thus delimiting similarities among these seemingly disparate family members (Oseguera et al, 2007;Jara-Oseguera et al, 2008). However, it remains unclear whether TRPV1 is also susceptible to extracellular inhibition by quaternary ammonium compounds.…”
Section: Introductionmentioning
confidence: 79%
“…To more directly assess the role of charge in TRPV1 inhibition, we characterized extracellular block by the quaternary permanently charged amines, TEA and TMA, which have been instrumental in the structure-function study of potassium channel pore regions. More recently, these compounds have been successfully used to help define the structure and basic biophysical properties of the intracellular TRPV1 channel pore (Oseguera et al, 2007;Jara-Oseguera et al, 2008). In our current study, similar to results with both lidocaine and QX-314, extracellular application of TEA produced a reduction in capsaicin-evoked inward currents, albeit with substantially higher affinity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the underlying cause of these observed cholesterol decreases in capsaicin-induced rTRPV1 currents, we performed noise analysis on rTRPV1 channels (37) in the presence and absence of cholesterol. Fig.…”
Section: Increased Membrane Cholesterol Decreased Capsaicin-induced Rmentioning
confidence: 99%
“…Biological physics research at Universidad de Sonora [25][26][27][28][29] has been growing well in recent years. Although institutions like the Instituto de Fisiología Celular [30][31][32] at UNAM and the Center for Research and Advanced Studies (Cinvestav) offer graduate programs in biophysics, their emphasis is more in the biological side of the subject [32,33]. With regards to BP, Cinvestav's physics department is already developing a research core [34][35][36][37][38][39], which other departments at Cinvestav are also doing research in biological physics and related issues [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Some Historical Remarks On Biological Physics Méxicomentioning
confidence: 99%